Electromyographic Patterns of Muscle Activation During Running with Different Footwear at Different Speeds in Nulliparous Women: A Secondary Analysis - María García-Arrabé; Fabien Guerineau; Beatriz Ruiz-Ruiz; Javier López-Ruiz; Mónica García-Mateos; María-José Giménez (Sensors)
With the global increase in women’s participation in running, understanding factors like footwear in performance and injury prevention has become essential. Minimalist shoes (MSs) and traditional shoes (TSs) influence muscle activation patterns, affecting running technique. Proper coordination of the core muscles is essential for efficient stride and posture. This study analyzed muscle activation in nulliparous women running in MSs and TSs at different speeds and explored the correlations with age and BMI. A crossover clinical trial assessed the EMG activation of the lumbar erector (LE), gluteus maximus (GM), pelvic floor, and internal oblique (IO) muscles during treadmill running at 6, 9, and 11 km/h. Fifty-one healthy women (26.55 ± 5.11 years; body mass index (BMI): 21.29 ± 2.07 kg/m2) participated. The protocol included a warm-up, 30 s runs at each speed, and a 5-minute washout between trials. The statistical analyses included Wilcoxon, Friedman, and Spearman’s correlation tests. GM and IO showed the highest activation (p < 0.001) regardless of the footwear or speed. No significant differences were found between MSs and TSs. Weak-to-moderate correlations emerged between BMI and LE muscle activation with MSs, and between BMI and IO with both footwear. Significant correlations were also found with IO activations, but none with PF muscles. The correlations between personal variables, shoe types, and muscle activation suggest that individual and external factors may influence neuromuscular modulation, impacting injury prevention and personalized interventions.